HUBUNGAN PENGETAHUAN TERHADAP PERILAKU PENGGUNAAN GREEN PACKAGING DI MASYARAKAT KOTA BANDUNG, JAWA BARAT - Nahda Amalia; Yosini Deliana; Erna Rachmawati; Sri Fatimah (Universitas Galuh Ciamis, 2021)
Environmental problems can occur due to human activities. Bandung City is a densely populated area and a tourist attraction that can cause environmental problems such as plastic waste. The largest volume of plastic waste in Bandung City is contributed from retail, traditional markets, and the people who use plastic bags. This study aims to determine the relationship between knowledge and behavior of using green packaging as an effort to reduce plastic waste in Bandung City. This research belongs to the type of quantitative research with survey and analysis methods using pearson correlation. The result shows that the higher level of public knowledge about green packaging does not have a good effect on the behavior of using green packaging. The dominant factor that is considered by the public in recognizing and using green packaging is social media and the surrounding social environment. Some people have also begun to try to use green packaging by bringing their own shopping bags, using drinking bottles and lunch boxes themselves when traveling, and are willing to educate people around to use green packaging to help preserve the environment.